1999
DOI: 10.1038/16476
|View full text |Cite
|
Sign up to set email alerts
|

The oncogene and Polycomb-group gene bmi-1 regulates cell proliferation and senescence through the ink4a locus

Abstract: The bmi-1 gene was first isolated as an oncogene that cooperates with c-myc in the generation of mouse lymphomas. We subsequently identified Bmi-1 as a transcriptional repressor belonging to the mouse Polycomb group. The Polycomb group comprises an important, conserved set of proteins that are required to maintain stable repression of specific target genes, such as homeobox-cluster genes, during development. In mice, the absence of bmi-1 expression results in neurological defects and severe proliferative defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
1,293
6
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,431 publications
(1,360 citation statements)
references
References 28 publications
48
1,293
6
2
Order By: Relevance
“…Furthermore, we recently reported that expression of exogenous Bmi-1 in NHOK led to significant extension (2.7 fold) of replicative life span but did not efficiently downregulate the expression of p16 INK4A (Kim et al, 2006). It is possible that Bmi-1 targets other important regulators of cell division in NHOK, such as p14 ARF or p15 INK4B , as previously suggested (Jacobs et al, 1999). Several recent studies also showed that the aberrant Bmi-1 expression is not necessarily associated with downregulation of p16 INK4A expression (Dukers et al, 2004;Breuer et al, 2005).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Furthermore, we recently reported that expression of exogenous Bmi-1 in NHOK led to significant extension (2.7 fold) of replicative life span but did not efficiently downregulate the expression of p16 INK4A (Kim et al, 2006). It is possible that Bmi-1 targets other important regulators of cell division in NHOK, such as p14 ARF or p15 INK4B , as previously suggested (Jacobs et al, 1999). Several recent studies also showed that the aberrant Bmi-1 expression is not necessarily associated with downregulation of p16 INK4A expression (Dukers et al, 2004;Breuer et al, 2005).…”
Section: Discussionmentioning
confidence: 76%
“…Bmi-1 protein was weakly detected in NHOK cultured in serum-free KGM and was not altered by the culture conditions (data not shown). As Bmi-1 is known to negatively regulate the expression of p16 INK4A in some cells (Jacobs et al, 1999), we checked for the correlation between the expression levels of Bmi-1 and p16 INK4A in our experimental system. Bmi-1 protein expression level was notably higher in most of the OSCC cell lines compared with that of NHOK, but did not correlate with the expression level of p16 INK4A , which correlated more closely with the human papillomavirus (HPV) infection status (Table 1).…”
Section: Bmi-1 Is Overexpressed In Oscc Cells and Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…After confirmation by restriction digestion and DNA sequencing, the sites introduced were used to allow domain exchange by standard recombinant techniques. These chimaeric HIF-a sequences were transferred into the retroviral vector pLZRS-IRES-GFP (Jacobs et al, 1999). Retroviral production and infection of target cells were conducted as previously described (Raval et al, 2005).…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…These events include DNA damage (DiLeonardo et al, 1994;Chen et al, 1995;Robles and Adami, 1998), as well as perturbations to chromatin organization (Ogryzko et al, 1996;Jacobs et al, 1999;Itahana et al, 2003;Narita et al, 2003). They also include the expression of certain oncogenes (Serrano et al, 1997;Zhu et al, 1998;Dimri et al, 2000) that deliver supraphysiological mitogenic signals to cells, and the overexpression of certain tumor suppressor genes (Sugrue et al, 1997;McConnell et al, 1998;Dai and Enders, 2000;Dimri et al, 2000;Beausejour et al, 2003).…”
Section: Causes Of Senescencementioning
confidence: 99%